The Development of Muslim Military Thought to the Liberation of Jerusalem in 1187 AD - Mohd Amin, Muhammad Husni (Journal of Al-Tamaddun, 2025)
This study examines the development of Muslim military thought from the early military encounters to the liberation of Jerusalem in 1187 A.D. Through historical and textual analysis, comparative conceptual mapping, and close reading of five key texts, Mukhtaṣar fī Siyāsat al-Ḥurūb, al-Aḥkām al-Sulṭāniyyah, Nahj al-Maslūk fī Siyāsat al-Mulūk, Tabṣirat Arbāb al-Albāb, and al-Tadhkirah al-Ḥarawiyyah fī al-Ḥiyal al-Ḥarbiyyah, the research traces how military ethics, governance, logistics, and strategy evolved in response to Byzantine, Crusader, and internal challenges. Drawing on manuscript sources and critical editions, the study highlights the integration of religious legitimacy, administrative order, and tactical adaptation in figures like Nūr al-Dīn Zangī and Ṣalāḥ al-Dīn al-Ayyūbī. Key findings include the role of the Sunnī revival in renewing strategic coherence and the layered interaction between legal theory, statecraft, and technical expertise. Limitations include uneven textual preservation and gaps in commentary, but the analysis affirms the strategic depth of Islamic military tradition during the aforementioned periods.